Effectiveness of tobacco control television advertising in changing tobacco use in England: a population‐based cross‐sectional study - Sims, Michelle; Salway, Ruth; Langley, Tessa; Lewis, Sarah; McNeill, Ann; Szatkowski, Lisa; Gilmore, Anna B. (Wiley, 2014)
AIM: To examine whether government‐funded tobacco control television advertising shown in England between 2002 and 2010 reduced adult smoking prevalence and cigarette consumption.